Evaluation of patients’ satisfaction after class III orthognathic surgery - Magro-Filho, Osvaldo [UNESP]; Goiato, Marcelo Coelho [UNESP]; Oliveira, Derly Tescaro Narcizo [UNESP]; Martins, Lidia Pimenta [UNESP]; Salazar, Marcio [UNESP]; De Medeiros, Rodrigo Antonio [UNESP]; Dos Santos, Daniela Micheline [UNESP] (JCDR Research and Publications, 2015)
Background: Well-planned orthognathic surgery improves psychological health, aesthetics and function of patients. Aim: The present study aimed to investigate patients’ satisfaction after orthognathic surgery by means of a satisfaction questionnaire before and after surgery. Materials and Methods: A total of 29 patients was selected (17 women and 12 men), with a mean age of 28 years, randomly selected from a private clinic at Araçatuba – São Paulo by two investigators. Anamnesis and clinical examination were performed. Subjects with facial deformities submitted to orthodontic treatment before and after orthognathic surgery with a minimum post-surgery period of 6 months, answered a satisfaction questionnaire composed of 10 questions regarding dental and facial aesthetics. In this study, the maximum satisfaction score was 10. Results: Regarding aesthetics, two satisfaction parameters were investigated: dental and facial. For all indices, the average satisfaction was up to score 7. Conclusion: According to the results, it can be concluded that orthognathic surgery has been an effective treatment for dentofacial deformities, aesthetics and functional problems, what was verified by pre and postoperative questionnaire application.
Keywords: Aesthetic; Class III Angle’s classification; Psychology